Bipolar life between two extremes - Juenger, Ernst; Jamison, Kay R.; Kidder, Margot; Films for the Humanities (Firm) (Princeton, NJ Films for the Humanities & Sciences, 2010)
"...This program examines the lives of people who have struggled for decades with bipolar disorder, once known as manic depression. Through case studies and discussions of recent research, the film shows how each patient has overcome the grip of debilitating despair and hyperactive euphoria, and how advances in psychology and neuroscience are helping such individuals lead better, more productive lives." -- Container.
This disc is a recorded DVD and may not play on all DVD players or drives.
Originally produced in 2010.
Kay Redfield Jamison, Margot Kidder.
DVD-R ; NTSC format ; stereo.
Keywords: Manic-depressive illness; Manic-depressive illness -- Treatment; Documentary films; Nonfiction films; Feature films; Feature films -- United States; Documentary films